Mental health literacy practices within Australian football league next generation academy clubs: An exploratory study - Diamond, S.; Wallace, L.; English, M.; Caperchione, C. M. (International Journal of Sports Science & Coaching, 2023)
Purpose To explore and describe the extent and quality of Mental Health Literacy (MHL) resources, information and education currently available within the Australian Football League (AFL) Next Generation Academy (NGA) programs and identify limitations/gaps in existing MHL practices within these programs.